Principal Strategies for Managerial Supervision to Enhance Teacher Discipline in Madrasah Ibtidaiyah - Herman, Herman; Zahraini, Zahraini; Rahmattullah, Rahmattullah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the approach taken by madrasah ibtidaiyah principals to enhance teacher discipline through the use of managerial oversight. To create a consistent culture of discipline in the classroom, managerial supervision is crucial. There is still a disconnect between the academic notions of supervision and their practical application, especially at madrasahs in the Pidie region. A qualitative descriptive methodology was used in this study, which included document analysis, observations, and interviews. The results show that, in spite of obstacles including a lack of professional development and environmental difficulties, principals use a variety of supervisory techniques to deal with teacher discipline concerns. To improve teacher discipline in primary Islamic schools, the study finds that contextualized policies and focused training are essential for bolstering management supervision.